Are gastroenterologists willing to implement imaging-guided surveillance for Barrett’s esophagus? Results from a national survey - Appannagari, Anoop; Soudagar, A. Samad; Pietrzak, Constance; Sharma, Prateek; Gupta, Neil (Endoscopy International Open, 2015)
Introduction: The American Society for Gastrointestinal Endoscopy (ASGE) has published a Preservation and Incorporation of Valuable Endoscopic Innovations (PIVI) statement on incorporating an imaging-guided surveillance protocol to replace the current practice of four-quadrant biopsies every two centimeters for Barrett’s esophagus (BE) surveillance. We sought to determine if current gastroenterologists would be willing to apply these changes to their practice and identify any barriers to implementation.Methods: We collected data using surveys that were distributed at two national meetings and using a random selection process emailed surveys to members listed in the American Gastroenterological Association directory. Physicians from a variety of practice settings participated. Primary outcomes of our study included determining whether clinicians would be willing to accept an imaging-based surveillance protocol, their reasons for not doing so, and whether a financial incentive would be persuade them to implement the protocol. Continuous variables were reported as mean ± standard deviation. Categorical variables were summarized with percentages and 95 % confidence intervals.Results: Gastroenterologists (172) completed the survey; and 140 (81.4 %) of them stated they would implemented the PIVI recommendations into practice. Using a multivariate analysis of the data, physicians who reported a financial incentive for submitting biopsy specimens to pathology were less likely to implement the PIVI recommendations. The two main barriers to implementation of the protocol were medical-legal and financial reasons. Of the 32 gastroenterologists who were not willing to implement the imaging-guided surveillance protocol, 20 (62.5 %) stated that they would implement it if there were a financial incentive.Discussion: The PIVI statement focuses on re-evaluating our current method of surveillance for BE. The results of our survey show that gastroenterologists may be willing to implement an imaging-guided surveillance program, but concerns regarding financial compensation and proper training in advanced imaging techniques remain.